Pontine hemorrhage presenting as Foville’s syndrome - Stephen, Mary; ., Jayasri; P. J., Harigaravelu; ., Baranitharan (International Journal of Advances in Medicine, 2021)
Foville’s syndrome, also known as inferior medial pontine syndrome is one of the rare brainstem stroke syndromes with only few cases reported worldwide occurring due to involvement of the infero-medial aspect of pons. Condition is characterised by various cluster of neurological features as a result of defect in multiple vital areas like cortico spinal tract, medial lemniscus, middle cerebral peduncle, facial nerve and abducens nerve involvement. We reported one such rare case of a patient with no known systemic co-morbidity, who presented with sudden onset diplopia, lagophthalmos and contralateral weakness of limbs. On evaluation with computed tomography imaging, hemorrhage at the level of inferior pons was found. Patient subsequently treated and commenced on physiotherapy for rehabilitation.